Prevalence, Awareness, Treatment, and Control of Hypertension in the Southern Cone of Latin America - Rubinstein, Adolfo L. (Am J Hypertens, 2016)
BACKGROUND: Hypertension is the leading global preventable risk factor for premature death. While hypertension prevalence has been declining in high-income countries, it has increased continuously in low- and middle-income countries. METHODS: We conducted a cross-sectional survey in 7,524 women and men aged 35–74 years from randomly selected samples in 4 cities (Bariloche and Marcos Paz, Argentina; Temuco, Chile; and Pando-Barros Blancos, Uruguay) in 2010–2011. Three blood pressure (BP) measurements were obtained by trained observers using a standard mercury sphygmomanometer. Hypertension was defined as a mean systolic BP ≥140mm Hg and/or diastolic BP ≥90mm Hg and/or use of antihypertensive medications. RESULTS: An estimated 42.5% of the study population (46.6% of men and 38.7% of women) had hypertension and an estimated 32.5% (36.0% of men and 29.4% of women) had prehypertension. Approximately 63.0% of adults with hypertension (52.5% of men and 74.3% of women) were aware of their disease condition, 48.7% (36.1% of men and 62.1% of women) were taking prescribed medications to lower their BP, and only 21.1% of all hypertensive patients (13.8% of men and 28.9% of women) and 43.3% of treated hypertensive patients (38.1% of men and 46.5% of women) achieved BP control. CONCLUSIONS: This study indicates that the prevalence of hypertension is high while awareness, treatment, and control are low in the general population in the Southern Cone of Latin America. These data call for bold actions at regional and national levels to implement effective, practical, and sustainable intervention programs aimed to improve hypertension prevention, detection, and control.